The Relationship between Numeric Ability and Students' Critical Thinking Skills in Physics Subjects - Hikmah Awaliyah (Universitas Muhammadiyah Makassar, 2019)
This research was an ex-post facto with correlational analysis that aimed to analyze and testing the level of numerical ability and critical thinking skill was achieved by the students of X class at SMA Negeri 8 in Gowa and the relationship between the two variables. Population this research were all students of X class at SMA Negeri 8 in Gowa, the sampling technique was random sampling obtained 92 respondens. The data was analyzed by descriptive statistical analysis and inferential statistical analysis included normality test, linearity test and the correlation of product moment test. Based on this research, it can be concluded that the level of numerical ability of students were in medium category, the level of critical thinking skill was in low category and there was positive and significant correlation between numerical ability and critical thinking skill of students of classes X class SMA Negeri 8 in Gowa.Keywords: numerical ability, critical thinking skillsPenelitian ini merupakan penelitian ex-post facto yang bersifat analisis korelasional yang bertujuan untuk menganalisis dan menguji tingkat kemampuan numerik dan Keterampilan Berpikir Kritis yang dicapai peserta didik kelas X SMA Negeri 8 Gowa, serta hubungan antara kedua variabel tersebut. Populasi dalam penelitian ini adalah seluruh peserta didik kelas X SMA Negeri 8 Gowa, sampel penelitian diambil secara acak dengan teknik random sampling sebanyak 92 responden. Teknik analisis data yang digunakan adalah analisis statistik deskiptif dan analisis statistik inferensial yang meliputi uji normalitas, uji linearitas dan uji korelasi product moment. Dari hasil penelitian dapat disimpulkan bahwa tingkat kemampuan numerik peserta didik berada dalam kategori sedang, tingkat keterampilan berpikir kritis berada dalam kategori rendah, dan terdapat hubungan positif yang signifikan antara kemampuan numerik dengan keterampilan berpikir kritis peserta didik pada mata pelajaran fisika kelas X SMA Negeri 8 Gowa.Kata kunci: kemampuan numerik, keterampilan berpikir kritis